Physical activity, sedentary behaviour, dietary pattern and metabolic snydrome among breast cancer survivors - Syed Muhammad Amirfaiz Syed Ali
Breast cancer (BC) urvivors are linked with higher risk of having metabolic syndrome (MetS) which affects their overall survival. However, extensive study on MetSassociated factors like physical activity (PA), sedentary (SED) behaviour and certain dietary pattern (DP) among BC survivors in Malaysia is scarcely reported. Thus, this study investigated MetS prevalence and its association with objectively measured P A, SED behaviour and DP among BC survivors in East Coast of Peninsular Malaysia. In this cross-sectional study BC survivors were recruited from two tertiary hospitals in Terengganu and Kelantan using purposi e sampling method. P A was objectively assessed for seven days using ActivPAL3 accelerometers, while sociodemographic and clinical data were acquired via self-administered questionnaire and medical records. Anthropometric measurements and blood samples were taken to assess metabolic profiles, and MetS was diageesed according to the Harmonised criteria. Food intake was assessed using food frequency questi rire. DP was derived using Reduced Rank was assessee UMllO 100U trequency questionnaire. DP was derived using Reduced Rank Regression (RRR) with dietary energy density (DED), saturated fat (SF) and dietary fibre (DF) as response variables. Association between P A, SED behaviour and DP with MetS was analysed using multiple logistic regression. The overall pr valence of MetS among the 95 BC survivors (age 53.7 ± 7.6 years) in this study was 50.5% (95% Confidence Interval, CI: 40.6-60.5). Most BC survivors had abdominal obesity (80.0%), whilst the highest prevalent component in those with MetS was dyslipidaemia (91.2%). Except for cancer stage, no significant difference was observed in sociodemographic and clinical data between those with and without MetS. Besides, BC survivors with MetS had significantly higher weight, waist circumference, body mass index and body fat percentage. In P A assessment, only 80 BC survivors with adequate valid P A data were included in the analysis. BC survivors with MetS had significantly higher number of prolonged SED bouts (>30 min) and average SED bouts duration than those without MetS. Additionally, those without any MetS component had significantly higher number of shorter standing bouts «10 min) per day. Independent of SED time, moderate-to-vigorous intensity PA and other confounders, MetS was inversely associated with shorter standing bouts «10 min) (odds ratio, OR:0.64, 95% CI: 0.42- 0.99) and shorter SED bouts (10-30 min) (OR:0.63, 95% CI: 0.44-0.90). In DP assessment, RRR analysis extracted high-DED, high-SF, low-DF DP. This DP was positively associated with sugar-sweetened drinks and fat-based spread, and was inversely associated with fruits, total vegetables, green leafy vegetables and seafoods. Across the quartiles of DP z-score, no significant difference was observed in basic soci demographic, anthropometric, and metabolic profiles as well as number of MetS component met. In the adjusted models, both the RRR-derived DP and its key food groups were not associated with MetS. This study suggested that MetS prevalence among the BC survivors was higher than the national prevalence, with increasing standing activities and shorter SED bouts to be protective towards MetS. However, no association between DP and MetS was observed among the BC survivors in this study.